Installation of Ocean Wave Recorder at Trivandrum (MAUSAM, 1959)
This paper deals with the installation of the Ocean Wave Recorder carried out by the Indian Naval Physical Laboratory. Details of the pressure type of underwater wave recorder, the choice of the site for the installation and the actual details of the installation are dealt with. A brief review of the naval applications of ocean wave studies is also given.